Wizerunki aktorów kina niemego w Hollywood (Bara - Pickford - Fairbanks) = Images of the silent film period`s actors in Hollywood (Bara - Pickford - Fairbanks) - Malczyk, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sketch is an attempt to discuss the phenomenon of stars creation images in the times of silent movies, its aim is to explain the creation of celebrities portraits. The article presents a brief outline of cinema history (the production of pioneer movies, the birth of Hollywood, the development of distribution networks, the rise of movie stars) and the process of creating images of actors/actress on the example of well?known then contemporary artists careers, e.g. Theda Bara, Mary Pickford and Douglas Fairbanks. Thanks to putting on their life facts an expanded mechanism of control over particular careers of the audiencje`s favourite idols of the first half of the 20th century is revealed.
Keywords: kino nieme; kreowanie gwiazd filmowych; Bara, Theda (aktorka amerykańska; 1885-1955); Pickford, Mary (aktorka amerykańska; 1892-1979); Fairbanks, Douglas (aktor amerykański; 1883-1939); silent movies; movie stars creation